Anglo-Scottish and Anglo-Welsh Diplomacy: 927-1154 - Smith, James (2023)
Anglo-Scottish and Anglo-Welsh diplomacy in 927-1154 has been underrepresented in dedicated studies of medieval diplomacy, receiving most of its scholarly attention from more general works of English, Scottish and Welsh history, with each national approach often contradicting the interpretations of the others. In response, this study provides in-depth analysis of diplomacy with the goal of illuminating kings’ social relationships, foreign policies and political aims. It has two primary focuses: comparing Anglo-Welsh and Anglo-Scottish relations, and determining the extent to which relations shifted from the Anglo-Saxon period to the Anglo-Norman one. Using an interdisciplinary and comparative framework, five significant themes of diplomatic practice are analysed: meeting places, objects, marriages, diplomats and exiles. Overall, Anglo-Welsh relations were characterised by frequent Welsh submissions to kings of England, whereas Anglo-Scottish relations were more variable, involving both English dominance and relative Anglo-Scottish equality. Furthermore, diplomacy does reveal some changes to relationships post-Norman Conquest. However, these broad conclusions are not the whole story, with exceptions and nuances highlighted throughout. In addition, this study has wider implications, since the conclusions drawn here not only relate to other medieval diplomatic relationships, but also to diplomacy in the modern world, which, with the rise of non-state diplomatic actors, increasingly resembles pre-state interactions.